Darkness Alliance with the International Police Organization Drug Dealing - Abdulameer Aziz , Wael; Jabbar Kredi, Prof.Dr.Ali (Basra studies journal, 2023)
Sharif The International Criminal Police Organization is one of the specialized international organizations and has an interest in international cooperation to combat common law crimes. It works in accordance with its basic law and data processing system. It has goals that it seeks to achieve, the most important of which is the fight against crime and its prevention. And the development of means of communication and cooperation between member states, taking into account the principles of the Universal Declaration. One of the most prominent crimes that the criminal organization is working to combat is drug crimes, Because, it is one of the crimes of the transnational organization, which is an international, regional and global problem that threatens human societies with the collapse , The criminal organization has technical mechanisms to achieve its goals in combating drug trafficking. The most prominent of which is the mechanism of international bulletins issued by the organization, which is a request for international cooperation addressed to member states with different colors of notices according to their different purpose and importance , The second mechanism is the controlled delivery mechanism, which is one of the relatively modern mechanisms and it is not only limitted to the criminal organization.But, this organization is the only police organ that can cross the borders of the state in cooperation with other central offices that belong to the General Secretariat of the criminal organization .